Voltage Stability and Reactive Power Sharing in Inverter-Based Microgrids with Consensus-Based Distributed Voltage Control - Schiffer, Johannes; Seel, Thomas; Raisch, Joerg; Sezi, Tevfik (IEEE Transactions on Control Systems Technology, 2016)
We propose a consensus-based distributed voltage control (DVC) that solves the problem of reactive power sharing in autonomous inverter-based microgrids with dominantly inductive power lines and arbitrary electrical topology. Opposed to other control strategies available thus far, the control presented here does guarantee a desired reactive power distribution in steady state while only requiring distributed communication among inverters, i.e., no central computing nor communication unit is needed. For inductive impedance loads and under the assumption of small phase angle differences between the output voltages of the inverters, we prove that the choice of the control parameters uniquely determines the corresponding equilibrium point of the closed-loop voltage and reactive power dynamics. In addition, for the case of uniform time constants of the power measurement filters, a necessary and sufficient condition for local exponential stability of that equilibrium point is given. The compatibility of the DVC with the usual frequency droop control for inverters is shown and the performance of the proposed DVC is compared with the usual voltage droop control via simulation of a microgrid based on the Conseil International des Grands Réseaux Electriques (CIGRE) benchmark medium voltage distribution network.
CRIS-Team Scopus Importer:2021-03-31
Keywords: Consensus algorithms; distributed cooperative control; droop control; inverters; microgrid control; microgrid stability; multiagent systems; power sharing; secondary control; smart grid applications; voltage stability